Mutagenicity of 5-aza-2′-deoxycytidine is mediated by the mammalian DNA methyltransferase - Jackson-Grusby, Laurie (The National Academy of Sciences of the USA, 1997)
The cytosine analog 5-aza-2′-deoxycytidine has been used clinically to reactivate genes silenced by DNA methylation. In particular, patients with β-thalassemia show fetal globin expression after administration of this hypomethylating drug. In addition, silencing of tumor suppressor gene expression by aberrant DNA methylation in tumor cells may potentially be reversed by a similar regimen. Consistent with its function in maintaining tumor suppressor gene expression, 5-aza-2′-deoxycytidine significantly reduces intestinal tumor multiplicity in the predisposed Min mouse strain. Despite its utility as an anti-cancer agent, the drug is highly mutagenic by an unknown mechanism. To gain insight into how 5-aza-2′-deoxycytidine induces mutations in vivo, we examined the mutational spectrum in an Escherichia coli lac I transgene in colonic DNA from 5-aza-2′-deoxycytidine-treated mice. Mutations induced by 5-aza-2′-deoxycytidine were predominantly at CpG dinucleotides, which implicates DNA methyltransferase in the mutagenic mechanism. C:G→G:C transversions were the predominant class of mutations observed. We suggest a model for how the mammalian DNA methyltransferase may be involved in facilitating these mutations. The observation that 5-aza-2′-deoxycytidine-induced mutations are mediated by the enzyme suggests that novel inhibitors of DNA methyltransferase, which can inactivate the enzyme before its interaction with DNA, are needed for chemoprevention or long term therapy.